مآلات مقدمات التفاسير بين الميول الأيديولوجية وتحديات العصر - Abdul Rahman Hussein Obeid; Adnan Mohamed Yusoff (Centre of Quranic Research, Universiti Malaya, 2024)
Introductions of Quranic commentaries are keys to understand the methods of interpreters, which could be theological method, juristic, linguistic, political or social methodology. Introduction to Quranic interpretation began with short linguistic and rhetorical show and fallen into the trap of long expound of Quranic issues. In fact, the stagnancy of interpretation means a doubtless death of its introduction, therefore, modernizing the commentaries introduction is necessity for several considerations. Some important regards for such modernization are emersion of new issues like thematic interpretation, political and social concerns and the most important is purposes of Islamic interpretation (Maqasid al-Tafsir). One of those purposes is seeking harmony between modern sciences and many scientific verses of the holy Quran. Other purposes that should be underlined are issues of citizenship, rights of minorities and educational challenges. The interpreter should be aware of handling these issues and at the same time avoid any type of propaganda for political interest and avoid falling into the trap of long introductions that deal with well-discussed issues and could be a published as separate book.